Influential factors on gray brocket deer (Mazama gouazoubira) activity and movement in the Pantanal, Brazil - Grotta-Neto, Francisco [UNESP]; Peres, Pedro H.F. [UNESP]; Piovezan, Ubiratan; Passos, Fernando C.; Duarte, José M.B. [UNESP] (Oxford University Press (OUP), 2019)
One of the major challenges in studies of activity and movement ecology is discovering how and why animals behave differently in certain environments. The gray brocket deer (Mazama gouazoubira) is widely distributed in the Neotropic region. In the Brazilian Pantanal wetland, gray brocket deer inhabit a unique landscape with varying ecotypes arranged in a mosaic, where seasonal flooding alters resource availability for the deer. Documenting animal activity and movement can be the key to understanding how a species interacts with its dynamic environment. We used data from accelerometers and characteristics of movement on six GPS-monitored gray brocket deer in the Pantanal wetland to investigate how habitat type, periods of the day, and cycles of flooding and drought affect activity, movement behavior, and displacement. Deer exhibited the lowest activity and encamped movement in closed habitat during diurnal and nocturnal periods, suggesting resting and foraging behaviors. The highest activity and exploratory movement occurred in open habitats, and potentially was related to deer searching for locations with greater resource availability. Individuals were displaced the most during floods, which was a response to access feeding sites that were free of water. Our results not only represent an unprecedented and refined view of the activity and movement behavior of brocket deer, but they also stress the importance of preserving multiple habitat types for species that express variable foraging strategies in heterogeneous landscapes.
Keywords: Accelerometers; Behavioral strategies; Brazilian wetland; Brocket deer; Elusive species; Mazama gouazoubira; Telemetry